The Analysis Study of Relationship of Breast Arterial Calcifications on Mammography to Predict Elevated Risk of Coronary Artery Disease: A Comprehensive Systematic Review - Rendi Rafsanjani; Bintara Ayu Putri; Mutiara Nurul Mahabbah (International Medical Journal Corp. Ltd, 2025)
Background: Breast arterial calcifications (BAC) are medial arterial calcifications visualized as linear